Tinjauan Krimonologi Terhadap Pelaku Kejahatan yang Dilakukan oleh Remaja dalam Komunitas Geng Motor Ditinjau dari Control Social Theory (Studi Kasus di Kabupaten Karawang) - Rana Dewi Siauta, Putri; Gagarin Akbar, M. Gary; Abas, Muhamad (Dinasti Review Publisher, 2024)
Criminology is a science that studies crime or specifically studies criminals. The criminological theory used in this research is Social Control Theory. According to Walker Reckless, bad behavior among teenagers is caused by a combination of internal and external control. Such as family, education, and dominant groups. Criminology focuses on the study of criminal behavior and criminals. This research aims to determine the causes of teenagers in the motorbike gang community committing crimes and the mitigation efforts carried out by the police. The method used is empirical juridical with an explanatory descriptive research type with data analysis using deductive logic. Data was obtained through interviews, with motorcycle gang members, police officers and direct observation in the field, and literature studies from various sources such as books, articles and legislation. The research results show that the factors that cause motorbike gang perpetrators to commit crimes consist of internal factors such as emotional instability and the influence of alcohol and drugs, and external factors such as family conditions, social environment and the economy. Countermeasures carried out by the police include preventive measures, namely efforts carried out before a crime occurs and repressive measures, namely efforts carried out by the police after a crime occurs.